Comparative study on the effect of different high-frequency chest wall oscillation and back patting modes on sputum excretion in patients with severe pneumonia - Tang, Bing; Gao, Bin; Tang, Li; Li, Yunying; Xiong, Xiaomin; Wang, Boyuan; Xu, Zhe; Xiao, Gexin; Xiao, Zunxiong (Frontiers in Medicine, 2025)
BackgroundThe effect of different backslapping parameters on sputum discharge in SP patients is unclear.ObjectiveTo investigate the effects of different back-patting modes on sputum clearance from the lungs of SP patients. To provide a theoretical basis for future clinical care and development of critical care robots.MethodsThe patients with severe pneumonia in ICU of Guangyuan tertiary hospital were selected as the study object, and according to the specific conditions of the patients, different back-patting methods were selected and given different back-patting intensity, back-patting frequency, back-patting times, back-patting times, back-patting times, and back-patting times, respectively, to compare and analyse the effects of the different back-patting methods on the patient’s expectoration effect, blood oxygen concentration, and lung signs.ResultsFinally, 143 patients with severe pneumonia were included. The volume of sputum expectoration, sputum viscosity, and blood oxygen saturation were significantly higher with different back patting patterns (p < 0.05), and the effective rate of treatment of pulmonary signs was significantly higher (p < 0.05).ConclusionSpecific high-frequency chest wall shock back-patterning can effectively improve sputum expectoration in SP patients, helping to restore lung function and reduce hospital stay.